2017
DOI: 10.1007/s11023-017-9455-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-Dominant Causation in Mind and Brain, and Its Implication for Questions of Generalization and Replication

Abstract: The dominant assumption about the causal architecture of the mind is, that it is composed of a stable set of components that contribute independently to relevant observables that are employed to measure cognitive activity. This view has been called component-dominant dynamics. An alternative has been proposed, according to which the different components are not independent, but fundamentally interdependent, and are not stable basic properties of the mind, but rather an emergent feature of the mind given a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…One possible explanation for this pattern of results is that multifractal estimates indicate unevenness with time, and the unevenness with time found in context stimuli might serve to produce the unevenness with time found in the “GA” responses. Said another way, the failure to replicate the simpler, multifractal-free effects showing that coarticulation for coarticulation need not be troubling because the nonlinear interactions across time scale in the measured behaviors—both in speech context and in participants' “GA” responses—are classically statistical mechanisms known to produce intermittent, nonstationary, and irregular results over average (Wallot and Kelty-Stephen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this pattern of results is that multifractal estimates indicate unevenness with time, and the unevenness with time found in context stimuli might serve to produce the unevenness with time found in the “GA” responses. Said another way, the failure to replicate the simpler, multifractal-free effects showing that coarticulation for coarticulation need not be troubling because the nonlinear interactions across time scale in the measured behaviors—both in speech context and in participants' “GA” responses—are classically statistical mechanisms known to produce intermittent, nonstationary, and irregular results over average (Wallot and Kelty-Stephen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, our results with respect to HRV complexity may begin to shed some light on this question. Informed by some of our prior work with young children (Berry & Stallworthy, 2018), as well as a growing literature with adults (e.g., Kelty-Stephen, Stirling, & Lipsitz, 2016; Wallot & Kelty-Stephen, 2018), we hypothesized that the internal organization of the HRV time series would become more pronounced in the context of more effortful regulation. For example, using HRV data collected during the administration of a battery of EF tasks in a different sample, we found that fractal complexity within the optimal pink noise range (~1) was associated with better EF performance than either more random (~0.8) or rigid time series organization (~1.5), yet only when children were actively challenged by the given task.…”
Section: Discussionmentioning
confidence: 99%
“…These assumptions allow 1) generalizing group-level results to individual cases and 2) isolating the presumed building blocks of psychopathology, justifying the search for a 'root cause'. Although these assumptions are strongly criticized (Fisher et al, 2018;Molenaar, 2009;Wallot & Kelty-Stephen, 2017), they are still reflected in group-level research designs where the between-person variation in a psychopathological outcome is modeled as the sum of a set of independent predictors. Our complex adaptive systems approach assumes that psychopathology is a dynamic pattern, rather than a static condition.…”
Section: The Structure Of Psychopathologymentioning
confidence: 99%